The Effect of Digital Comic Books on Reading Comprehension - Firnanda, Aris; Usman, Muhammad; Faudi, Faudi (English LAnguage Study and TEaching, 2023)
This experimental research aims to find out the effectiveness of digital comic books in reading skills at SMP Bunga Matahari Banda Aceh in the academic year 2021/2022. The samples of this research were 16 students of ninth-grade students who were divided into two groups (one group as an experimental group and one group as the control group). The researcher administered a pre-test before the treatment to collect data about the students reading preliminary scores. Then, the teacher taught reading by using comics in two meetings at the experimental group and conducted a post-test to collect data about the student's reading ability after they learned reading by using narrative-based comics. Meanwhile, the students in the control group were taught reading by using the traditional method in two meetings and then they were given a post-test. Then, the pre-test and post-test test scores were analyzed by using N-Gain scores. The mean score pre-test of the control group was 75.50, and the experimental group was 70.63, the mean score post-test of the control group was 82.50 and the mean score post-test of the experimental group increased to 89.50. Based on the result of the research, it could be concluded that teaching reading narrative text by using digital comics could improve the student's reading comprehension of narrative text.